Pengaruh Dewan Komisaris Independen, Komite Audit, Kepemilikan Institusional, Profitabilitas dan Kompensasi Rugi Fiskal Terhadap Tax Avoidance pada Perusahaan Manufaktur Barang Konsumsi yang Terdaftar di BEI Tahun 2019-2022 - Astriyasana, Della Prisca Devi; Wafirotin, Khusnatul Zulfa; Muntiah, Nur Sayidatul (Universitas Katolik Soegijapranata, Semarang, 2024)
This study aims to determine the influence of the independent board of commissioners, audit committee, institutional ownership, profitability and fiscal loss compensation on tax avoidance in consumer sector manufacturing companies listed on the IDX. This type of research is quantitative research. The population in this research is consumption sector companies listed on the Indonesia Stock Exchange for four years starting from 2019-2022. The sampling method used was purposive sampling method and the sample size was 31 companies. The data used is annual financial report data of consumer sector manufacturing companies obtained from the official website (www.idx.co.id). The data analysis technique used is multiple linear regression. The research results show that partially Profitability and Fiscal Loss Compensation have a significant effect on tax avoidance, the Independent Board of Commissioners, institutional ownership, audit committee have no effect on tax avoidance.Keywords : Independent Board of Commissioners; Audit Commitee;Institusional Ownership; Profitability;and Fiscal Loss Compensation.